2021
DOI: 10.5116/ijme.606a.e83d
|View full text |Cite
|
Sign up to set email alerts
|

Alternative career pathways for international medical graduates towards job market integration: a literature review

Abstract: Objectives:To inform the current level of research about alternative career pathways for international medical graduates and synthesize knowledge of the barriers, facilitators and potential outcomes of alternative career pathways for international medical graduates. Methods: We searched MEDLINE, EMBASE, Scopus, and Google Scholar for relevant publications to February 2020. From 809 articles, after two levels of screening, 23 articles were selected. We conducted thematic content analysis and reported the findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…It has been reported that IMGs generally seldom considered seeking any career other than becoming a physician [ 7 ], and this usually leads to delay in seeking any other career [ 8 ]. This delay can deprive IMGs of time that may be required to prepare for any new career and obtain any required related work training or experience to allow for success in a decent alternative career [ 9 , 10 ]. Most studies on IMGs only focused on the areas of work [ 11 , 12 ] and experience of the licensed IMGs [ 13 ] and barriers and struggles [ 14 ] to licensing for the unlicensed IMGs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that IMGs generally seldom considered seeking any career other than becoming a physician [ 7 ], and this usually leads to delay in seeking any other career [ 8 ]. This delay can deprive IMGs of time that may be required to prepare for any new career and obtain any required related work training or experience to allow for success in a decent alternative career [ 9 , 10 ]. Most studies on IMGs only focused on the areas of work [ 11 , 12 ] and experience of the licensed IMGs [ 13 ] and barriers and struggles [ 14 ] to licensing for the unlicensed IMGs.…”
Section: Introductionmentioning
confidence: 99%
“…However, naturally, because of their physician background, most IEPs’ professional networks are generally limited to those in the physician/physician licensure realm [ 25 ]. Another important challenge is the lack of understanding of potential alternative careers and the transferable skills IEPs can utilize in those jobs [ 26 ]. This lack of knowledge obscures them from identifying an alternative career that suits their skills, aptitude, and individual perspectives (e.g., financial constraints, family responsibilities, etc.…”
Section: Alternative Career Pathways In the Health And Wellness Sectormentioning
confidence: 99%
“…For this professional group, a suitable alternative career could be a job where they can use their health-related knowledge and technical skills. However, there is a lack of understanding, information, and organizational support on ACPs for IMGs [ 8 10 ]. Our program of research is built around the objective to identify and facilitate suitable alternative career pathways available for IMGs in Canada.…”
Section: Objectivementioning
confidence: 99%